Review: Sabine Kittel (2006). "Places for the Displaced" [Biographical Coping Patterns of Female Jewish Nazi Concentration Camp Survivors Living in the USA] - Angela Schwarz (Forum: Qualitative Social Research, 2008)
This sociological, or rather socio-psychological, study offers a glimpse of the strategies for survival devised by female Jewish prisoners during and after their imprisonment in a Nazi concentration camp. It draws its conclusions from ten narrative interviews conducted with survivors living in the US. Readers versed in Holocaust research and survivor literature will find little new information in the chapters on the interviewees’ experiences of the concentration camps. In contrast, the chapters on life after liberation offer new insight into individual strategies. They point to parallels in narrating Holocaust experience and the life led thereafter—both narratives are characterized by the attempt to attribute sense to them. However, before a result like this can be generalized to describe a "generation," as the author suggests, many more interviews must be conducted and analyzed. URN: urn:nbn:de:0114-fqs0901293